Characterizing flame stability and radiative heat transfer in non-swirling oxy-coal flames using different multiphase modeling frameworks. (15th November 2019) - Seidel, Trevor; Krishnamoorthy, Gautham; Seames, Wayne S.
Abstract: The ability of two multiphase modeling frameworks (Euler-Lagrangian and Euler-Euler) to capture the experimentally observed flame ignition characteristics in non-swirling oxy-coal flames were investigated. The interphase interaction terms were modeled employing identical phenomenological laws. Simulations of inert particles were carried out first and were found to yield identical predictions across both frameworks. Next, user-defined functions were utilized to: model the diffusional and kinetic resistances associated with the heterogeneous char oxidation (in the Euler-Euler framework), the non-gray effects of gas radiation, and the variations in the radiative properties of the solid phase (in the Euler-Lagrangian framework). Only the Euler-Euler framework was able to capture the experimental observed trends in flame stand-off as a function of oxygen concentration in the primary burner. The interval between the devolatilization and char combustion processes varied between the two frameworks and were a contributing factor to the prediction differences. Representing the coal PSD by a single granular phase in the Eulerian framework was deemed adequate for capturing flame stand-off since solving additional phase equations did not significantly impact the flame stand-off predictions. Further, the experimentally observed effects of: primary oxidizer composition variations, secondary oxidizer temperature and wall temperature on flame stand-off were also adequately predicted reasonably well by the Euler-Euler framework. Radiation was the dominant mode of heat transfer in these flames with the radiant heat loss fraction (Radiative heat loss/Total chemical heat release) determined to be 0.6 for both flames. Radiation from the participating gases accounted for 75% of the total radiative heat transfer.